READINESS OF ELEMENTARY SCHOOL TEACHERS IN APPLYING PROTOTYPE CURRICULUM - Acesta, S.P, M.Pd, Dr. Arrofa; Oktaviani, Ndaru Mukti; Wulandari, Isnaini (UNIKU PRESS, 2023)
ABSTRACTThe prototype curriculum is a curriculum that encourages learning according to students' abilities, provides space for character development and basic competencies. Teacher readiness has an important role in ensuring the implementation of the prototype curriculum. The purpose of this study was to determine the readiness of elementary school teachers to implement the prototype curriculum in Kuningan District. This research is included in the type of survey research with a quantitative descriptive approach. Techniques used to collect the data in this study were questionnaires and interviews. Data analysis techniques for the data obtained from the questionnaire will be processing carried out in the following stages 1) editing, 2) scoring, 3) tabulation. The results showed in general percentage of readiness of elementary school teachers to implement the prototype curriculum in Kuningan District is 73.60%. That’s means overall percentage of readiness of elementary school teachers to implement the prototype curriculum in Kuningan District are in a good category. For each dimension obtained the percentage results on the emotive-attitudinal dimension for elementary school teachers specifically teaching grade I in Kuningan district is 95.20%, the percentage on the cognitive-readiness dimension is 71.29%, and the percentage on the behavioral readiness dimension is 78,56 %.Keywords: readiness; teacher; curriculum prototype